A novel method for the laboratory workup of anaphylactic transfusion reactions in haptoglobin‐deficient patients. Issue 4 (23rd January 2020) - Thoren, Katie L.; Avecilla, Scott T.; Klimek, Virginia; Goss, Cheryl
Abstract : BACKGROUND: Patients with congenital haptoglobin deficiency can develop anti‐haptoglobin antibodies after exposure to blood products, and they can suffer from life‐threatening anaphylactic transfusion reactions. Here, we present a case of a 57‐year‐old Chinese male with myelodysplastic syndrome who manifested an anaphylactic transfusion reaction during the transfusion of platelets. The only abnormality detected during his reaction laboratory workup was an undetectable haptoglobin level in the absence of evidence of hemolysis. STUDY DESIGN AND METHODS: Surface plasmon resonance (SPR) was explored as a method to be able to detect the presence of anti‐haptoglobin antibodies in serum. First, haptoglobin was immobilized to the surface of an SPR sensor chip. The patient's serum sample was injected, and the binding response was monitored in real time. Serum samples from five healthy volunteers were used as negative controls. Binding specificity was assessed in competition experiments using soluble haptoglobin. Anti‐IgG, ‐IgA, ‐IgM, ‐IgD and ‐IgE antibodies were used to identify the antibody isotype. RESULTS: An IgG anti‐haptoglobin antibody was detected in the patient's serum with SPR. CONCLUSION: SPR provided a rapid, readily available method for the detection of an IgG anti‐haptoglobin antibody in an anhaptoglobinemic individual. This confirmed the underlying etiology of the anaphylactic nonhemolytic transfusion reaction and justified the necessity of stringently washed cellular products for all future transfusions and strong caution for future use of plasma‐containing products.